Unveiling maternal morbidity: insights from a descriptive cross-sectional study of postpartum women - Thomas, Riya; Soman, Surya; Abraham, Bevan; Mathew, Jomol; Jacob, Philip (International Journal of Basic & Clinical Pharmacology, 2024)
Background: The repercussions of obstetric problems and inadequate management during birth are carried over into the normal 42-day postpartum period, adding to the burden of maternal ill-health, which also includes levels of maternal mortality and complications during postpartum period. Our study was done to determine the common morbidities that postpartum subjects undergo and make awareness to health care practitioners and prevent complicated scenarios. Methods: Cross-sectional descriptive study was conducted in rural areas of Eraviperoor Grama Panchayath community pathanamthitta, Kerala, India. There were 150 people in the study’s sample. The study involved women who are in their postpartum phase (months 0–8). Results: Our study of 150 participants found that 65% of deliveries were through C-sections. Despite 56% of postpartum women expressing high satisfaction with their overall health, concerns include nipple cracks (80%), urinary tract infections (56%), bacterial infections (12.5%), stitch allergies (6.5%), anemia (18%), leg edema or erythema (2%), difficulty urinating (18%), burning during urination (13%), and breast pain (4%) as prevalent morbidities. Conclusions: The present findings enable healthcare professionals to examine postpartum women’s physical and emotional health more comprehensively, enabling them to enhance their quality of life.